Method for manufacturing positive electrode active material and positive electrode active material
By mechanically grinding and heating treatment of Li1.2M1.0.4M2.0.4O2 material, it is transformed into an irregular rock salt-type crystal structure, which solves the capacity and cycle characteristics of layered rock salt-type positive electrode materials, and realizes the application of high-performance positive electrode materials.
Patent Information
- Application Number
- JP2023123208
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-07
AI Technical Summary
The actual capacity of the existing layered rock salt type LiMO cathode active material is low and has poor circulation characteristics, making it difficult to meet the needs of high-performance lithium-ion batteries.
The Li1.2M1.0.4M2.0.4O2 (M1 is Cr or Ni, M2 is Mn or Ti) material synthesized by solid phase reaction is mechanically ground and heated to be transformed into an irregular rock salt-type crystal structure, improving electrochemical activity and cyclic characteristics.
The discharge capacity and cycle stability of the positive electrode active material are significantly improved, and high-performance positive electrode material applications are achieved.
Smart Images

Figure 2025019548000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a positive electrode active material by mechanically pulverizing and then heating to obtain the positive electrode active material, a treatment method for improving the cycle characteristics of the positive electrode active material, and the positive electrode active material. [Background technology]
[0002] As a positive electrode material for next-generation lithium-ion batteries, materials using layered rock-salt LiMO2 (where M is vanadium, chromium, manganese, iron, cobalt, or nickel) as a positive electrode active material are attracting attention. It has been reported that these layered rock-salt compounds are synthesized by solid-state reaction and then mechanically crushed (mechanical milling) to form nanoparticles, which changes the crystal structure of the layered rock-salt type of rhombohedral crystal system to an irregular rock-salt type of cubic crystal system, thereby improving the electrochemical activity of LiMO2 synthesized by solid-state reaction, which was previously considered inactive (see Patent Document 1). In addition, LiCrO2, a solid solution of Li2MnO3, is reported to have a high electrochemical activity. 1.2 Cr 0.4 Mn 0.4 O2 has also been reported as a layered rock salt type positive electrode active material. This positive electrode active material has a theoretical capacity of 323mAh / g, which is higher than the theoretical capacity of LiVO2 (298mAh / g), LiCrO2 (297mAh / g), LiMnO2 (285mAh / g), LiCoO2 (274mAh / g), and LiNiO2 (275mAh / g). However, the actual capacity was only about 180mAh / g. 1.2 Cr 0.4 Mn 0.4 There has been a demand for a method to improve the electrochemical activity, such as the discharge capacity and cycle characteristics, of layered rock salt compounds such as O2. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2022-140018 A Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present invention is to provide a method for obtaining a positive electrode active material having excellent discharge capacity and cycle characteristics. Another object of the present invention is to provide a positive electrode active material having excellent discharge capacity and cycle characteristics. [Means for solving the problem]
[0005] The present inventors have developed Li ZnO, which is an oxide containing lithium and two transition metals and has a layered rock-salt crystal structure. 1.2 Cr 0.4 Mn 0.4 The inventors have focused on compounds such as LiCrO2 and O2 and have been developing them as positive electrode active materials. As in the case of LiCrO2, these compounds were synthesized by solid-state reaction, and when the synthesized compounds were mechanically crushed, the crystal structure changed from layered rock salt type to irregular rock salt type, and although the initial discharge capacity increased compared to before crushing, the cycle characteristics decreased. Therefore, the inventors further investigated and unexpectedly found that a positive electrode active material with increased discharge capacity and excellent cycle characteristics could be obtained by heat-treating the crushed material after mechanical crushing. The present invention was thus completed.
[0006] That is, the present invention is specified by the following items. (1) Li synthesized by solid-state reaction 1.2 M1 0.4 M2 0.4 A method for producing a positive electrode active material, comprising mechanically crushing O2 (wherein M1 is Cr or Ni, and M2 is Mn or Ti) and then heating the crushed O2. (2) The method for producing a positive electrode active material according to (1) above, wherein M1 is Cr and M2 is Mn. (3) The method for producing a positive electrode active material according to (1) or (2) above, wherein the heating temperature is 400 to 900°C. (4) Li with an irregular rock-salt crystal structure 1.2 M1 0.4 M2 0.4A treatment method for improving cycle characteristics of a positive electrode active material, comprising heating O2 (wherein M1 is Cr or Ni, and M2 is Mn or Ti) at a heating temperature of 400 to 900°C. (5) Li 1.2 M1 0.4 M2 0.4 A positive electrode active material represented by the formula: O2 (wherein M1 is Cr or Ni, and M2 is Mn or Ti) and having a crystallite diameter of 80 to 300 Å. (6) The positive electrode active material according to (5) above, wherein M1 is Cr and M2 is Mn. Effect of the Invention
[0007] According to the manufacturing method of the present invention, a positive electrode active material having excellent discharge capacity and cycle characteristics can be manufactured. According to the treatment method of the present invention, the cycle characteristics of the positive electrode active material can be improved. The positive electrode active material of the present invention has excellent discharge capacity and cycle characteristics. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a diagram showing the results of X-ray diffraction measurement of Comparative Examples 1 to 6. [Diagram 2] 2 is a diagram showing SEM images of Comparative Examples 1 and 4 and Examples 1 to 4. L-LCMO is Comparative Example 1, m-LCMO is Comparative Example 4, 500-LCMO is Example 1, 600-LCMO is Example 2, 700-LCMO is Example 3, and 800-LCMO is Example 4. [Diagram 3] FIG. 3 is a diagram showing the configuration of the battery used in the electrochemical evaluation. [Figure 4] FIG. 4 is a diagram showing charge / discharge curves of Comparative Examples 1 to 6. [Diagram 5] FIG. 5 is a graph showing the cycle characteristics of Comparative Examples 1 to 6. [Figure 6] FIG. 6 is a diagram showing the results of X-ray diffraction measurement of Examples 1 to 4 and Comparative Example 4. [Figure 7] FIG. 7 is a diagram showing charge / discharge curves of Examples 1 to 4 and Comparative Example 4. [Figure 8]FIG. 8 is a graph showing the cycle characteristics of Examples 1 to 4 and Comparative Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The method for producing a positive electrode active material of the present invention is to synthesize Li by a solid-state reaction. 1.2 M1 0.4 M2 0.4 The manufacturing method is characterized by mechanically crushing and further heating 102 (wherein M1 is Cr or Ni, and M2 is Mn or Ti). In the present invention, the solid-phase reaction is a reaction in which two or more solid raw materials are mixed and then reacted at high temperature to obtain the target product. By mixing a raw material containing Li, a raw material containing M1, and a raw material containing M2 and sintering them, Li is obtained. 1.2 M1 0.4 M2 0.4 O2 can be obtained. The raw material containing Li is not particularly limited, but examples thereof include Li salts such as carbonates, nitrates, sulfates, and phosphates of Li. The raw material containing M1 is not particularly limited, but examples thereof include M1 oxides such as Cr2O3 and NiO. The raw material containing M2 is not particularly limited, but examples thereof include M2 oxides such as Mn3O4 and TiO2. These raw materials are mixed and fired, and firing conditions such as firing temperature and firing time, as well as other production conditions, are determined according to the Li 1.2 M1 0.4 M2 0.4 The usual conditions for producing O2 can be followed and selected appropriately. For example, Li 1.2 Cr 0.4 Mn 0.4 In the case of O2, the firing temperature can be 700 to 1000° C., and prior to main firing at the firing temperature, preliminary firing can be performed, for example, at 300 to 600° C. The firing can be performed in air or in an inert gas, and the firing time can be appropriately selected depending on the firing temperature, but for example, the main firing time can be 8 to 30 hours and the preliminary firing time can be 3 to 6 hours.
[0010] In the present invention, mechanical pulverization means pulverizing Li by applying mechanical energy.1.2 M1 0.4 M2 0.4 The term "pulverization" refers to the pulverization of O2, and is not particularly limited as long as it is a pulverization method that adds mechanical energy, but examples thereof include methods using roller mills, hammer mills, pin mills, pulverizers using pulverization media, and the like. Examples of pulverizers using pulverization media include rotary mills, vibration mills, planetary mills, attritors, and bead mills, and examples of the material of the pulverization media include ceramics such as zirconia and metals such as stainless steel, and examples of the shape of the pulverization media include ball-shaped (including beads) and rod-shaped. As the pulverization media, multiple types of pulverization media with different materials, shapes, or sizes may be used. A pulverizer that uses a ball-shaped pulverization media is collectively called a ball mill, and a ball mill is suitable as a pulverizer used in the pulverization treatment in the present invention. In particular, a planetary ball mill is preferred. The pulverization treatment in the present invention may be a dry or wet type, and the pulverization atmosphere may be an air atmosphere or an inert gas atmosphere, but the pulverization treatment can be performed in a simpler dry or air atmosphere. In addition, there is no need to perform heating or the like during pulverization.
[0011] In the mechanical crushing process of the present invention, the Li 1.2 M1 0.4 M2 0.4 It is preferable to pulverize LiO2 so that the average primary particle diameter is 50-600 nm, 50-500 nm, 100-400 nm, or 100-300 nm. It is also preferable to pulverize LiO2 so that the primary particle diameter is in the range of 50-600 nm, 50-500 nm, 100-400 nm, or 100-300 nm. The average primary particle diameter and the primary particle diameter can be determined by image analysis of SEM images of the particles after the pulverization treatment. It is preferable to measure the primary particle diameter of at least 100 particles from the SEM images, and pulverize LiO2 so that 80% or more of the particles are in the above range, and it is more preferable to pulverize LiO2 so that 90% or more of the particles are in the above range. In the pulverization treatment of the present invention, the pulverization of LiO2 after pulverization is performed. 1.2 M1 0.4 M2 0.4It is preferable to grind the LiO2 so that the crystallite diameter is 120 Å or less, 100 Å or less, 90 Å or less, or 70 Å or less. The lower limit of the crystallite diameter is not particularly limited, but examples thereof include 40 Å or more, 50 Å or more, and 60 Å or more. Examples of the crystallite diameter include 40 to 120 Å, 50 to 100 Å, and 60 to 90 Å. The crystallite diameter can be determined by X-ray diffraction measurement. The grinding conditions, such as the grinding time, are determined by the amount of LiO2 after grinding. 1.2 M1 0.4 M2 0.4 The average primary particle size or the primary particle size or the crystallite size of LiO2 can be selected to be within the above range. 1.2 M1 0.4 M2 0.4 O2 may be pre-pulverized (coarsely pulverized) before being pulverized to nano size. In the manufacturing method of the present invention, Li synthesized by solid-state reaction is 1.2 M1 0.4 M2 0.4 By mechanically crushing O2, Li with an irregular rock-salt crystal structure was obtained. 1.2 M1 0.4 M2 0.4 Mechanical pulverization improves the discharge capacity when used as a positive electrode active material, but the cycle characteristics are poor.
[0012] Li in the present invention 1.2 M1 0.4 M2 0.4 The molar ratios of Li, M1, M2 and O in O2 may differ from the theoretical values in the range of 0 to 0.01. 1.2 M1 0.4 M2 0.4When expressed as LixM1yM2zO2, O2 includes those in which x, y, and z are in the ranges of x=1.2±0.01, y=0.4±0.01, and z=0.4±0.01. The heating method in the manufacturing method of the present invention is not particularly limited as long as it is a method that can heat the pulverized material, and various heating methods can be used appropriately. Heating may be performed in an air atmosphere or an inert gas atmosphere, but it is preferable to perform it in an inert gas atmosphere such as argon. The heating temperature is preferably 400 to 900°C, and more preferably 500 to 800°C. The heating time can be appropriately selected depending on the heating temperature, and can be, for example, 0.5 to 5 hours, 1 to 3 hours, etc. The heating treatment in the manufacturing method of the present invention is performed to obtain Li after the heating treatment. 1.2 M1 0.4 M2 0.4 The heat treatment is preferably performed so that the crystallite diameter of LiO2 is 80 to 300 Å, and more preferably 90 to 260 Å. 1.2 M1 0.4 M2 0.4 The crystallite size of O2 can be determined by X-ray diffraction measurement. 1.2 M1 0.4 M2 0.4 It is believed that by heating O2, a layered rock salt type crystal structure is generated, and a nano-interface bond between the layered rock salt type and the irregular rock salt type is formed. By the heat treatment, it is possible to improve the cycle characteristics while maintaining the improved discharge capacity after crushing. The treatment method for improving the cycle characteristics of the positive electrode active material of the present invention is a method for treating Li2O3 having an irregular rock salt type crystal structure. 1.2 M1 0.4 M2 0.4 The present invention is characterized in that M1 is Cr or Ni, and M2 is Mn or Ti. The object of the treatment in the treatment method of the present invention is Li 1.2 M1 0.4 M2 0.4 There is no particular limitation as long as it is O2, and there is no limitation on the synthesis method. The heating method, heating temperature, other heating conditions, etc. in the treatment method of the present invention are the same as those in the production method of the present invention.
[0013] The positive electrode active material of the present invention is Li 1.2 M1 0.4 M2 0.4 O2 (wherein M1 is Cr or Ni, and M2 is Mn or Ti), and the crystallite size is preferably 80 to 300 Å, more preferably 90 to 260 Å. The positive electrode active material of the present invention preferably has an average primary particle size or a primary particle size in the range of 50 to 600 nm, 50 to 500 nm, 100 to 400 nm, or 100 to 300 nm. At least 100 primary particle sizes are measured by SEM images, and it is preferable that 80% or more of the particles are in the above range, and more preferably 90% or more of the particles are in the above range. The average primary particle size and the primary particle size can be measured by the same method as the method described above for the mechanical crushing treatment. The positive electrode active material of the present invention can be obtained by the manufacturing method of the present invention. The positive electrode active material of the present invention contains Li in an amount not interfering with the use as a positive electrode active material. 1.2 M1 0.4 M2 0.4 The positive electrode active material of the present invention may contain other components other than O2. The positive electrode active material of the present invention may be used as it is, or may be mixed or composited with other conductive materials to improve the conductivity of the electrode. Examples of other conductive materials include carbon sources such as acetylene black, graphite, and carbon nanotubes, and the positive electrode may be carbon-coated and used. A positive electrode can be produced by forming an active material layer of the positive electrode active material of the present invention on a current collector, and examples of the current collector include aluminum, titanium, nickel, stainless steel, and copper, and examples of the shape include plate, foil, net, and porous. When forming the positive electrode active material layer of the present invention on a current collector, a binder may be mixed and applied to the current collector. Examples of the binder include thermoplastic resins such as fluororesins such as polyvinylidene fluoride and polytetrafluoroethylene, and polyolefin resins such as polyethylene and polypropylene. The application method is not particularly limited as long as it is a method that can apply the positive electrode active material or a mixture of the positive electrode active material and the binder to the current collector. EXAMPLES
[0014] The present invention will be described in detail below with reference to examples of the present invention. The present invention is not limited to these examples.
[0015] [Examples 1 to 4] Lithium carbonate (Li2CO3), chromium (III) oxide (Cr2O3), and manganese (II, III) oxide (Mn3O4) were mixed so that the molar ratio of lithium, chromium, and manganese was 1.2:0.4:0.4. The mixture was pre-calcined in air at 500°C for 5 hours, and then calcined in air at 950°C for 12 hours to obtain layered rock salt Li 1.2 Cr 0.4 Mn 0.4 O2 was prepared. 1.2 Cr 0.4 Mn 0.4 O2 was placed in a planetary ball mill container together with 1.5 g of zirconia balls with a diameter of 3 mm (the atmosphere inside the container was air) and pulverized under the condition of 600 rpm (planetary ball mill device: Fritsch, Pulverisette 7). The pulverization time was 6 hours. The pulverized material was heated in an Ar atmosphere for 1 hour at 500°C in Example 1, 600°C in Example 2, 700°C in Example 3, and 800°C in Example 4 to obtain the positive electrode active materials of Examples 1, 2, 3, and 4.
[0016] [Comparative Example 1] Lithium carbonate (Li2CO3), chromium (III) oxide (Cr2O3), and manganese (II, III) oxide (Mn3O4) were mixed so that the molar ratio of lithium, chromium, and manganese was 1.2:0.4:0.4. The mixture was pre-calcined in air at 500°C for 5 hours, and then calcined in air at 950°C for 12 hours to obtain layered rock salt Li 1.2 Cr 0.4 Mn 0.4 O2 was prepared and used as the positive electrode active material of Comparative Example 1.
[0017] [Comparative Examples 2 to 6] Lithium carbonate (Li2CO3), chromium (III) oxide (Cr2O3), and manganese (II, III) oxide (Mn3O4) were mixed so that the molar ratio of lithium, chromium, and manganese was 1.2:0.4:0.4. The mixture was pre-calcined in air at 500°C for 5 hours, and then calcined in air at 950°C for 12 hours to obtain layered rock salt Li 1.2 Cr 0.4 Mn 0.4 O2 was prepared. 1.2 Cr 0.4 Mn 0.4 O2 was placed in a planetary ball mill container together with 1.5 g of zirconia balls with a diameter of 3 mm (the atmosphere inside the container was air) and pulverized under the condition of 600 rpm (planetary ball mill device: Fritsch, Pulverisette 7) to obtain the positive electrode active materials of Comparative Examples 2 to 6. The pulverization time was 1 hour in Comparative Example 2, 3 hours in Comparative Example 3, 6 hours in Comparative Example 4, 12 hours in Comparative Example 5, and 24 hours in Comparative Example 6.
[0018] (X-ray diffraction measurement) The positive electrode active materials obtained in Examples 1 to 4 and the positive electrode active materials obtained in Comparative Examples 1 to 6 were subjected to X-ray diffraction measurement (MiniFlex600, manufactured by Rigaku Corporation). The results of Comparative Examples 1 to 6 are shown in FIG. 1, and the results of Examples 1 to 4 are shown in FIG. 6. As shown in FIG. 1, in Comparative Example 1, Li 1.2 Cr 0.4 Mn 0.4 In contrast, in Comparative Examples 2 to 6, the peak of the 003 plane (2θ = 18°) disappeared, and Li 1.2 Cr 0.4 Mn 0.4 It can be seen that O2 has an irregular rock salt type crystal structure. On the other hand, from FIG. 6, in Examples 1 to 4, a peak appears at about 2θ=18°. 1.2 Cr 0.4 Mn 0.4O2 is thought to be in a state in which an irregular rock-salt type crystal phase and an amorphous phase are mixed, but in Examples 1 to 4, a layered rock-salt type crystal structure appears upon heat treatment, resulting in a state in which the layered rock-salt type and irregular rock-salt type crystal structures are mixed, and the layered rock-salt type and irregular rock-salt type crystal structures are thought to be joined at nano-interfaces.
[0019] (Measurement of particle size and crystallite size) The particle size and crystallite size of the positive electrode active materials obtained in Examples 1 to 4 and the positive electrode active materials obtained in Comparative Examples 1 and 4 were determined. The particle size was in the range of 2 to 2.5 μm in Comparative Example 1, but in the range of 100 to 300 nm in Comparative Example 4, in the range of 100 to 300 nm in Examples 1 and 2, and in the range of 100 to 500 nm in Examples 3 and 4. The crystallite size was 527 Å in Comparative Example 1, 60 Å in Comparative Example 4, 94 Å in Example 1, 101 Å in Example 2, 109 Å in Example 3, and 244 Å in Example 4. It can be seen from Comparative Example 1 and Comparative Example 4 that not only the particle size but also the crystallite size was reduced by the pulverization treatment. On the other hand, it can be seen from Comparative Example 4 and Examples 1 to 4 that the particle size does not change significantly due to the heat treatment, but the crystallite size is larger than after the pulverization treatment. However, the Li with a layered rock salt type crystal structure in Comparative Example 1 was 527 Å, 60 Å in Comparative Example 4, 94 Å in Example 1, 101 Å in Example 2, 109 Å in Example 3, and 244 Å in Example 4. 1.2 Cr 0.4 Mn 0.4 It is much smaller than the O2.
[0020] The particle size indicates the primary particle size determined using a scanning electron microscope (SEM) (JSM-7600F manufactured by JEOL Ltd.). SEM images of the positive electrode active materials obtained in Examples 1 to 4 and the positive electrode active materials obtained in Comparative Examples 1 and 4 are shown in FIG. 2. The crystallite size is determined by the Williamson-Hall method from two or more XRD peaks belonging to the XRD pattern of the obtained positive electrode active material (hereinafter also referred to as "WH size"). Specifically, the irregular rock salt type Li 1.2 Cr 0.4 Mn 0.4 Two or more XRD peaks attributable to O2, preferably disordered rock-salt Li 1.2 Cr 0.4 Mn 0.4For all XRD peaks attributable to O2, the following plots are made. The following linear approximation equation is determined by the least squares method of the obtained plots of multiple points, and the reciprocal of the y-intercept of the linear approximation equation is the crystallite size. <Plot> Y=(β sinθ) / λ X=sinθ / λ <First-order approximation formula> Y = 2η·X + (1 / ε) (1 equation) In these formulas, β is the half-width (°), θ is the diffraction angle (°), λ is the wavelength of the radiation source (nm), η is the non-uniform strain, and ε is the crystallite diameter (Å), and 1 / ε in the first-order approximation formula is the y-intercept. 1.2 Cr 0.4 Mn 0.4 The above plot was made using all the XRD peaks at 2θ = 38°, 44°, and 64° that are attributed to O2. 1.2 Cr 0.4 Mn 0.4 Similarly, for the crystallite size of O2, the above plot was made using all the XRD peaks at 2θ = 18°, 36°, 42°, 48°, 58°, 64°, 64.4°, and 68°, which are attributed to the layered rock salt type. 1.2 Cr 0.4 Mn 0.4 For the crystallite size of O2, the above plot was made using the XRD peaks at 2θ = 38°, 44°, and 64°, which are assigned to the disordered rock-salt type, and the XRD peak at 2θ = 18° ((003) plane), which is assigned to the layered rock-salt type.
[0021] (Evaluation of charge / discharge characteristics and cycle characteristics) Lithium ion batteries were produced using the positive electrode active materials obtained in Examples 1 to 4 and Comparative Examples 1 to 6, and the charge / discharge characteristics and cycle characteristics were evaluated. The lithium ion batteries were produced as follows. The positive electrode active materials obtained in Examples 1 to 4 and Comparative Examples 1 to 6 were mixed with acetylene black (manufactured by Denka Co., Ltd.) and polyvinylidene fluoride in a mass ratio of positive electrode active material:acetylene black:polyvinylidene fluoride of 80:15:5. The mixture was applied to aluminum foil, dried, and punched out to a diameter of 15 mm to produce a positive electrode (coated electrode). The amount of positive electrode active material carried in the positive electrode was 3 mg / cm. 2 The results are shown in FIG. 3. A coin battery was fabricated using a 15 mm diameter Li metal (Honjo Metal) for the negative electrode, polypropylene (Celgard) for the separator, 1M LiPF6 / EC:DMC (=1:1 vol%, Toyama Pharmaceutical) for the electrolyte, and a coin cell (2032 type) for the battery case, as shown in FIG. 3. Charge and discharge tests for Comparative Examples 1 to 6 were performed at a current density of 13 mA / g, a voltage range of 2.0 to 4.5 V, and 25°C. The obtained charge and discharge curves are shown in FIG. 4. Next, cycle tests for Comparative Examples 1 to 6 were performed at a current density of 13 mA / g, a voltage range of 2.0 to 4.5 V, 25°C, and 10 cycles. The results are shown in FIG. 5. The positive electrode active material (layered rock salt type Li 1.2 Cr 0.4 Mn 0.4 O2), only 180 mAh / g of discharge capacity was obtained, whereas the crushed positive electrode active materials of Comparative Examples 2 to 6 (irregular rock salt Li 1.2 Cr 0.4 Mn 0.4 In the case of Comparative Example 2, a high discharge capacity of 250 to 300 mAh / g was obtained in all cases. However, the positive electrode active materials of Comparative Examples 2 to 6 had poor cycle characteristics, and the discharge capacity retention rate at the 10th cycle (discharge capacity after the initial cycle / discharge capacity after 10 cycles) was 60% in Comparative Example 2, 64% in Comparative Example 3, 59% in Comparative Example 4, 59% in Comparative Example 5, and 47% in Comparative Example 6.
[0022] Further, the charge / discharge tests of Examples 1 to 4 and Comparative Example 4 were carried out at a current density of 26 mA / g, a voltage range of 2.0 to 4.5 V, and 25° C. The obtained charge / discharge curves are shown in FIG. 7. Next, cycle tests of Examples 1 to 4 and Comparative Example 4 were carried out at a current density of 26 mA / g, a voltage range of 2.0 to 4.5 V, 25° C., and 30 cycles. The results are shown in FIG. 8. The positive electrode active materials of Examples 1 to 4 which were heat-treated after the crushing treatment obtained high discharge capacities of 267 mAh / g in Example 1, 261 mAh / g in Example 2, 256 mAh / g in Example 3, and 259 mAh / g in Example 4, and furthermore, were excellent in cycle characteristics, and even at the 30th cycle, high discharge capacity retention rates (discharge capacity after initial cycle / discharge capacity after 30 cycles) of 64% in Example 1, 66% in Example 2, 71% in Example 3, and 78% in Example 4 were shown. [Industrial Applicability]
[0023] The manufacturing method of the present invention can easily obtain a positive electrode active material with high electrochemical activity, and therefore can be suitably used for manufacturing an active material that can be used for the positive electrode of a battery, such as a lithium ion secondary battery. The positive electrode active material of the present invention has high electrochemical activity and can therefore be suitably used for the positive electrode of a battery, such as a lithium ion secondary battery.
Claims
1. Li synthesized by solid-state reaction 1.2 M1 0.4 M2 0.4 O 2 (wherein M1 is Cr or Ni, and M2 is Mn or Ti), is mechanically crushed, and then heated.
2. 2. The method for producing a positive electrode active material according to claim 1, wherein M1 is Cr and M2 is Mn.
3. 3. The method for producing a positive electrode active material according to claim 1, wherein the heating temperature is 400 to 900° C.
4. Li with an irregular rock salt crystal structure 1.2 M1 0.4 M2 0.4 O 2 (wherein M1 is Cr or Ni, and M2 is Mn or Ti) at a heating temperature of 400 to 900° C.
5. Li 1.2 M1 0.4 M2 0.4 O 2 (wherein M1 is Cr or Ni, and M2 is Mn or Ti), and has a crystallite diameter of 80 to 300 Å.
6. 6. The positive electrode active material according to claim 5, wherein M1 is Cr and M2 is Mn.
Citation Information
Patent Citations
Manufacturing method for positive electrode active material and positive electrode active material
JP2022140018A